The Knowledge for Student Age 15-19 Abaout Impact Alcohol Consumption for the Function Reprodutor to Estudant class 11st - Barreto Amaral, Meriana; Guterres Correia, Avelino; Deus, Elisa de; Pereira, Natalia; Soares, Miguel; Almeida Oqui, Serafino de (Rifa'Institute, 2024)
Introduction: Alcoholic beverages kill over 3 million people worldwide each year. Based on the mortality rate caused by alcohol, it exceeds that caused by Human Immunodeficiency Virus, Tuberculosis, and Violence. Alcohol-related mortality includes liver diseases, cancer, violence, and drunkenness. Alcoholic drinks pose a global problem for communities worldwide. Objective: The Knowledge for student age 15-19 about impact alcohol consumption for the function reproduction to student class 11st. Method: This research method is a Descriptive Qualitative method The research was conducted in the General Secondary Education of 5 de Maio Becora, Christo Rei Subdistrict, Dili Municipality, Timor Leste. The total sample size is 270 people from classes A, B, C, and D. The independent variable is not specified. Results and Discussion: According to the results of this research shows that the majority of young people are less information about health and this is a point that contributes to the case of non-communicable diseases because alcohol contains a chemical which is a major cause of health. Human knowledge is very important to lead us to live a healthy life. Conclusion: From the results of the research showed that 8 young people have less knowledge about alcohol that many people consume in their lives, damage the heart, drugs that have a negative impact on health, face running, headache, what is not satisfying when there is no knowledge, damage people and bad impact on health 2 is the knowledge about alcohol that makes lanu and destroy the mind.